Intimal disruption affects drug-eluting cobalt-chromium stent expansion: A randomized trial comparing scoring and conventional balloon predilation. (15th October 2016) - Jujo, Kentaro; Saito, Katsumi; Ishida, Issei; Kim, Ahsung; Suzuki, Yuki; Furuki, Yuho; Ouchi, Taisuke; Ishii, Yasuhiro; Sekiguchi, Haruki; Yamaguchi, Junichi; Ogawa, Hiroshi; Hagiwara, Nobuhisa
Abstract: Background: Stent expansion remains one of the most important predictors of restenosis and subacute thrombosis, even with the use of drug-eluting stents. This study was designed to clarify the impact of lesion preparation on final stent expansion. Methods: Sixty-six consecutive patients were included in this trial, and ultimately 52 enrolled non-calcified de novo lesions were randomly assigned to undergo single predilation with either a semi-compliant scoring balloon or a semi-compliant conventional balloon. Lesions were treated with a single 2.5- to 3.0-mm cobalt–chromium everolimus-eluting stent under optical coherence tomography (OCT) guidance without post-stenting dilation. Stent expansion was defined as the ratio of OCT-measured minimum stent area to the predicted stent area. Results: Stent expansion was significantly higher after predilation by a scoring balloon (68.0% vs. 62.1%, p = 0.017) with similar stent lumen eccentricity (0.84 vs. 0.80, p = 0.18). Intimal disruption was induced significantly more frequently (68.0% vs. 38.4%, p = 0.035) and was more extensive in the scoring group (122° vs. 65°, p = 0.038). Lesions with intimal disruption after predilation achieved significantly higher stent expansion than that without it (67.7% vs. 61.6%, p = 0.023). One case in the conventional group required target lesion revascularization; however, any other adverse clinical events including death, myocardial infarction, and stent thrombosis were not observed up to 9 months after PCI in both groups. Conclusions: In this randomized study, pretreatment with a scoring balloon enhanced stent expansion partly through induction of intimal disruption. Clinical trial registration: URL:http://www.umin.ac.jp/ctr/index.htm . Unique identifier: UMIN000014176.